The Ẓāhirī Madhhab (3rd/9th-10th/16th century) : a textualist theory of Islamic law - Osman, Amr, 1978- (Studies in Islamic Law and Society, 2014)
In this book, Amr Osman seeks to expand and re-interpret what we know about the history and doctrine of the Ẓāhirī madhhab . Based on an extensive prosopographical survey, he concludes that the founder, Dāwūd al-Ẓāhirī, was closer in profile and doctrine to the Ahl al-Ra'y than to the Ahl al-Ḥadīth . Furthermore, Ibn Ḥazm al-Andalusī may have had a damaging effect on the madhhab , which never actually developed into a full-fledged school of law. By examining the meaning of ' ẓāhir ' and modern scholarship on 'literalism', he challenges the view that Ẓāhirism was literalist, proposing 'textualism' as an accurate reflection of its premises, methodology, and goals as a hermeneutical and legal theory.